Project Based Learning (PJBL) Learning Model on Creativity of Practical Learning Outcomes in Vocational Schools: Meta Analysis Study - Gusnita, wiwik; Ambiyar, Ambiyar; Syah, Nurhasan (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
The aim of education is to increase the effective and efficient values ​​of both teachers and students. Curriculum renewal is needed to develop learning models that are maximally effective and efficient for students to achieve optimal learning outcomes. The Project Based Learning learning model is an innovative learning model that refers to student skills through complex learning activities so that it can encourage student creativity to improve learning outcomes. However, based on the results of field analysis in several practical subjects, it was found that there were obstacles or barriers to being able to implement the Project Based Learning (PjBL) learning model. This research using analytical studies looks at the effects obtained when implementing the Project Based Learning learning model. The conclusion from this meta-analysis study is that there is quite a significant influence that the Project Based Learning learning model has on student creativity in vocational high schools and has not had a significant effect on elementary schools. This means that the Project Based Learning learning model only has a significant effect on secondary school students who have good spatial abilities.